IDENTITAS SOSIAL, NORMA KELOMPOK, KEPERCAYAAN DAN ONLINE HELPING BEHAVIOR PADA KOMUNITAS SOSIAL BERBASIS FACEBOOK - Sony Kusumasondjaja (MIX: JURNAL ILMIAH MANAJEMEN, 2016)
Abstract. AIMI (Association of Indonesian Breastfeeding Mothers) is one of the nonprofitentities in Indonesia that relies on its social media account to facilitate itsmembers to help and support each other in issues related with breastfeeding activities.This research investigates whether social identity, member’s trust to the group andother members, and group norms are the antecedents of online helping behavior inAIMI Facebook Group. Data was collected using online questionnaire posted on theAIMI online forum in Facebook. Respondents were AIMI members recruited usingjudgment sampling; which allowed only member who had posted their ideas orthoughts or comments in the AIMI online forum in Facebook. Findings suggest that thestronger the social identity shared among members of the community, the greater thetrust and group norms developed among the members. Greater trust and group normslead to greater likelihood of online helping behavior among the membersKeywords: social identity, online helping behavior, trust, community, social mediaAbstrak. AIMI (Asosiasi Ibu Menyusui Indonesia) adalah suatu lembaga non-profit diIndonesia yang mengandalkan akun media sosial mereka untuk memfasilitasianggotanya untuk saling mendukung dalam kegiatan-kegiatan yang berhubungandengan aktivitas menyusui. Penelitian ini menyelidiki apakah identitas sosial,kepercayaan anggota, dan norma kelompok merupakan anteseden online helpingbehavior pada AIMI Facebook Group. Data diperoleh dengan menyebarkan kuesioneronline yang diposting di Facebook page AIMI. Responden adalah anggota AIMIdirekrut melalui judgment sampling; dengan kriteria yang membatasi hanya anggotaAIMI yang pernah melakukan posting di forum tersebut yang direkrut sebagairesponden..Temuan penelitian ini menyatakan bahwa online helping behavior dapattercipta dari identitas sosial yang kuat, kepercayaan besar, dan norma kelompok diantara anggotanya.Kata Kunci: identitas sosial, online helping behavior, trust, community, media sosial